LIFT CONTROL WITH PROGRAMMABLE LOGIC CONTROLLER (PLC) SOFTWARE - KUEH, LEE HUI (Universiti malaysia sarawak (UNIMAS), 2001)
This report presents a ladder diagram to operate a designed lift model in a four-storey building model using the Programmable Logic Controller (PLC) system. A flowchart of the lift operation is drawn to implement the ladder diagram. A set of Input/Output (I/O) assignment has to be initialised. The PLC system configuration, features and components, and general specifications must be considered properly to translate the flowchart into the ladder diagram. The ladder diagram is translated into mnemonic codes for simulation. This is done to ensure the program is running efficiently and safe in the desired lift model